Children's Interest In Learning In Islamic Culture - Ahdar Ahdar; Wardana Wardana; Musyarif Musyarif (Jurnal Ilmiah POTENSIA, 2020)
Foster children's interest in learning according to Islamic education that is suitable for children who have extraordinary interests. This paper will also describe the interests and learning, and the factors that influence the emergence of interests and interests in the view of Islamic education. Likewise, the factors that are seen in fostering children's interest in learning will be raised, and the characteristics of interested children and obstacles in fostering children's interest in learning. This paper is analyzed using the literature method. This paper try to find out more about how to foster learning interests of children who have extraordinary interests will be explained about the need to pay attention to the interests of children who have potential who expect help from those who are entitled to help, and more importantly in growing children's interest is encouragement in more appropriate learning that, and more importantly the child to realize and actualize the interests that exist in each child